(3OjhGf QGTO Hf NejS GdYeGfjs - (3GdMHSj, QGTO Hf NejS Hf LeYI, J(B1150(3g`s ((3YHO Gddg Hf MehO Hf MGeO Hf SGdejf GdYPGdjs)
(3ChdgG (B:s
(3GdMeO ddg GdChd bHd cd TjAhHYO agPg ebOeI PcQgG GdTjN SdjeGf Hf HdYQHaj fSH GdTGYQ GdHdjZGdHGH GdChd aj GdeOGFM GdfHhjI hGdOYGA hGdJVQY Edi Gddg SHMGfg hJYGdi bGajI GdgeRI ef GdHMQ GdeLJKs
(3BNQgG (B:s
(3hGddg NjQ dg ef (B*** (3gPj GdHQjI WQG , OGhi GdQRGjG HYRe (B*** (3hGLYd eY GdYRe UHQGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 3 / 11s
(3eYLe GdeDdajf(B: 1 / 709s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs